Analysis of digitalization processes in the field of science of Russia - A. Volkov (State University of Management, 2020)
The essence of the processes of digitalization in the field of science of Russia has been considered, the specific issues of adaptation of science to the demands of the information society have been revealed, the readiness of the Informatization process of the Russian scientific sphere has been assessed. The criteria for the formation of the potential of digital technologies used in scientific and design work have been evaluated. The statistics of the state of development of high and knowledge-intensive technologies in General and information and communication technologies used in research and development, in particular, has been adduced.The complexities of determining indicators and classification of information and communication technologies used have been reviewed. The approaches to determining the statistics of the number of employees employed in computer science and related industries have been presented. The indicators of development of research and developments in the field of digital technologies have been investigated. The distribution of the employed in various sectors of the national economy has been given. An increase in the cost of importing technologies has been noted, which indicates a rise in the country’s technological dependence on sources of external (foreign) technologies. It has been noticed, that in the field of information and communication technologies, Russia had a significant profit from technology exports, which indicates the progressiveness of scientific developments in the field of digital technologies. The issues of financing research and development, shortcomings in the incentive mechanisms of the methods used and sources of funding have been considered. The state of educational processes, that form the personnel component of the digitalization of the economy, has been analysed.The results of information activity in the field of research and development will allow us to draw a conclusion about the lack of readiness of the sphere of research and development in the field of information and communication technologies in the organization of promotion and dissemination of digital technologies in the scientific field.